2001
DOI: 10.1523/jneurosci.21-05-01710.2001
|View full text |Cite
|
Sign up to set email alerts
|

Specific Roles of NMDA and AMPA Receptors in Direction-Selective and Spatial Phase-Selective Responses in Visual Cortex

Abstract: Cells in the superficial layers of primary visual cortex (area 17) are distinguished by feedforward input from thalamic-recipient layers and by massive recurrent excitatory connections between neighboring cells. The connections use glutamate as transmitter, and the postsynaptic cells contain both NMDA and AMPA receptors. The possible role of these receptor types in generating emergent responses of neurons in the superficial cortical layers is unknown. Here, we show that NMDA and AMPA receptors are both involve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 50 publications
0
40
0
Order By: Relevance
“…A previous study in anesthetized cats (23) supported the different roles of these glutamate receptors by showing that activation of AMPA-Rs added a relatively constant number of spikes to the firing rate of a neuron, whereas activation of the NMDA-R caused an increase in response gain. Similarly, a study on direction selectivity (43) showed that AMPA-R activity produces directionally selective responses, whereas NMDA-R activity amplifies neuronal responses evoked by a stimulus moving in the preferred direction. In other words, NMDA-Rs increase the firing rate of active cells and have little effect on neurons not driven by the visual stimulus.…”
Section: Discussionmentioning
confidence: 95%
“…A previous study in anesthetized cats (23) supported the different roles of these glutamate receptors by showing that activation of AMPA-Rs added a relatively constant number of spikes to the firing rate of a neuron, whereas activation of the NMDA-R caused an increase in response gain. Similarly, a study on direction selectivity (43) showed that AMPA-R activity produces directionally selective responses, whereas NMDA-R activity amplifies neuronal responses evoked by a stimulus moving in the preferred direction. In other words, NMDA-Rs increase the firing rate of active cells and have little effect on neurons not driven by the visual stimulus.…”
Section: Discussionmentioning
confidence: 95%
“…2 also illustrates that we use slow excitation in the synapses between cortical cells (see temporal coupling profiles). The total excitatory postsynaptic potential was the sum of an ␣-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) component and a N-methyl-D-aspartate (NMDA) component (27) with equal weight integrated over time. We found that, in networks where the cortical coupling is mediated only by AMPA, the strong cortical amplification led to large-amplitude global oscillations.…”
Section: Resultsmentioning
confidence: 99%
“…LGN/V1). Within V1, other NMDA-dependent processes, such as delayed GABAergic feedback, may also contribute to neuronal motion sensitivity (Rivadulla et al, 2001). Motion sensitivity deficits, as well as more general magnocellular dysfunction Kwon et al, 1991Kwon et al, , 1992, therefore may both be manifestations of proposed disturbances in glutamatergic and/or NMDA-dependent neurotransmission in schizophrenia.…”
Section: Discussionmentioning
confidence: 99%